Dissection of multibeam satellite communications with a large-scale antenna system toolbox - Arnau, Jesus; Carlos Mosquera (European Wireless 2014 (EW2014), 2014)
Current multibeam satellite systems consist of a very large number of spot beams. In this paper, we analyze them from the large scale MIMO perspective, and establish a comparison with massive MIMO systems. It will be shown that the large number of beams has important operational implications, and that it simplifies the analysis because it allows using asymptotic results. However, it will also be shown that multibeam satellite systems cannot be considered massive MIMO systems.
Keywords: dynacs; large-scale analysis; Massive MIMO; multibeam satellites; Multiuser detection; satcom